The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.2174/0929866522666150622101626
|View full text |Cite
|
Sign up to set email alerts
|

Smac-Derived Aza-Peptide As an Aminopeptidase-Resistant XIAP BIR3 Antagonist

Abstract: Abstract:The peptidic nature of anti-IAPs N-terminus Smac-derived peptides precludes their utilization as potential therapeutic anticancer agents. Recent advances in the development of novel Smacderived peptidomimetics and non-peptidic molecules with improved anti-IAPs activity and resistance to proteolytic cleavage have been reported and led to a number of candidates that are currently in clinical trials including LCL-161, SM-406/AT-406, GDC-0512/GDC-0917, and birinapant. As an attempt to improve the proteoly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Furthermore, in vivo studies demonstrated that SMAC mimetic peptides could enhance TRAIL-induced apoptosis in xenograft models (Simone Fulda, Wick, Weller, & Debatin, 2002). These studies were the first to prove that mimicking the N-terminus of SMAC could be an effective way to target IAPs and paved the way for the development of complex fusion and other synthetic peptides (A Elsawy, G Tikhonova, Martin, & Walker, 2015;Elsawy, Martin, Tikhonova, & Walker, 2013).…”
Section: Smac Mimeticsmentioning
confidence: 99%
“…Furthermore, in vivo studies demonstrated that SMAC mimetic peptides could enhance TRAIL-induced apoptosis in xenograft models (Simone Fulda, Wick, Weller, & Debatin, 2002). These studies were the first to prove that mimicking the N-terminus of SMAC could be an effective way to target IAPs and paved the way for the development of complex fusion and other synthetic peptides (A Elsawy, G Tikhonova, Martin, & Walker, 2015;Elsawy, Martin, Tikhonova, & Walker, 2013).…”
Section: Smac Mimeticsmentioning
confidence: 99%
“…Aza-peptides contain at least one amino acid in which the α-carbon atom is replaced by nitrogen . The semicarbazide substructure reduces conformational flexibility. , Several studies have revealed that the incorporation of aza-amino acids into bioactive peptides may result in a longer duration of action or higher potencies compared to the parent peptide. Aza-peptides can be prepared by the reaction of an N-protected, N′-substituted hydrazine with an isocyanate . However, the synthesis of aza-peptides on a solid phase is compromised by an intramolecular side-reaction of resin-bound isocyanates that results in the formation of hydantoins (Figure A), lowering the yields of the target compounds and requiring time-consuming purification .…”
Section: Resultsmentioning
confidence: 99%
“…Without purification, the isocyanates were treated with hydrazines 10 and 12 affording the benzyl-protected N-Fmoc-aza 1 -dipeptides in yields >70%. Subsequent ester cleavage by hydrogenation gave access to the N-Fmoc-aza 1dipeptides Fmoc-aza-Leu-Arg(Pbf)-OH (17), Fmoc-aza-Orn-(Boc)-Tyr(tBu)-OH (18), and Fmoc-aza-Orn(Boc)-Leu-OH (19). The dipeptides 17−19 were employed in solid phase synthesis under the same conditions as those for the standard Fmoc-protected amino acids, resulting in quantitative coupling efficiencies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Smac was first reported as a pro-apoptotic protein in July 2000 and is widely expressed in human normal tissues and primarily located in the cell mitochondria ( 29 ). Smac has been observed to act conversely to XIAP ( 37 , 38 ). Previous studies investigating Smac in numerous tumor tissues suggested that the low expression of Smac may inhibit the apoptosis of tumor cells ( 39 – 42 ).…”
Section: Discussionmentioning
confidence: 99%